CORRELATION BETWEEN PERCEPTIONS OF QUALITY ANTENATAL CARE SERVICES TO PATIENT SATISFACTION OF PREGNANT WOMEN DURING THE COVID-19 PANDEMIC - Desi Ratnasari; Ratna Dwi Jayanti; Reni I’tishom (Indonesian Midwifery and Health Sciences Journal, 2023)
Background: Quality antenatal care services play a very important role in reducing MMR and IMR. With quality antenatal care, mothers and babies can get essential services, identify risk factors immediately, and get access to emergency help amid the COVID-19 pandemic as it is now. The quality of health services is related to patient satisfaction. Satisfaction can provide a good start, create repeat patient visits and provide recommendations for other pregnant women patients. Objective: Analyzing the relationship between perceptions of the quality of antenatal care services and patient satisfaction of pregnant women at the Public Health Center during the COVID-19 pandemic. Method: this type of research is an observational analytic with a cross-sectional design. The number of samples is 73 respondents, the sample is taken by non-probability sampling with consecutive sampling technique. The independent variable is the perceived quality of antenatal services. The dependent variable is patient satisfaction. The instrument used was a google form questionnaire, and the data analysis using the Spearman rank test. Result: the majority of respondents gave good perceptions on the dimensions of reliability, responsiveness, assurance, empathy, and direct evidence. Respondents with good perceptions were more than half satisfied, while respondents with sufficient perceptions were mostly dissatisfied with antenatal care services. Spearman's rank test results for each dimension obtained P=0.001 (P<0.05). Conclusion: There is a significant relationship between perceptions of the quality of antenatal care services and patient satisfaction of pregnant women at the Public Health Center during the COVID-19 pandemic.. keyword : Perception, Quality of service, COVID-19